2012
DOI: 10.1152/ajpendo.00486.2011
|View full text |Cite
|
Sign up to set email alerts
|

SUMO downregulates GLP-1-stimulated cAMP generation and insulin secretion

Abstract: Rajan S, Torres J, Thompson MS, Philipson LH. SUMO downregulates GLP-1-stimulated cAMP generation and insulin secretion. Am J Physiol Endocrinol Metab 302: E714 -E723, 2012. First published January 10, 2012; doi:10.1152/ajpendo.00486.2011.-Glucagon-like peptide-1 (GLP-1)-based incretin therapy is becoming central to the treatment of type 2 diabetes. Activation of incretin hormone receptors results in rapid elevation of cAMP followed by enhanced insulin secretion. However, the incretin effect may be significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…These observations are in line with what my laboratory [14,18,19] and others [12,20] have shown using complementary models, including in human islets. We know, for example, that increasing SUMOylation blunts glucose-stimulated insulin secretion by directly inhibiting insulin exocytosis [14,21], and that islet Senp1 knockout results in glucose intolerance without affecting islet mass or insulin content [18].…”
Section: Sumoylation and The Isletsupporting
confidence: 92%
See 2 more Smart Citations
“…These observations are in line with what my laboratory [14,18,19] and others [12,20] have shown using complementary models, including in human islets. We know, for example, that increasing SUMOylation blunts glucose-stimulated insulin secretion by directly inhibiting insulin exocytosis [14,21], and that islet Senp1 knockout results in glucose intolerance without affecting islet mass or insulin content [18].…”
Section: Sumoylation and The Isletsupporting
confidence: 92%
“…SUMOylation at the plasma membrane is now reasonably well-appreciated as a mechanism regulating ion channels and receptors, including the glucagon-like peptide-1 receptor in beta cells [20]. My group and others have also shown that SUMOylation regulates exocytotic membrane fusion [14,23], and this appears to be mediated by direct SUMOylation of exocytotic proteins and consequent regulation of protein-protein interactions amongst members of the secretory machinery [21].…”
Section: Downstream Sumo-dependent Mechanisms In Isletsmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, SENP1 alone can enhance insulin exocytosis, but this action is blocked under oxidizing conditions (32). SUMOylation may play diverse roles in pancreatic islet biology (33), having recently been implicated in metabolism (34), incretin receptor signaling (35), excitability (36), and survival (37). Importantly, the role for SENP1 in insulin secretion and in vivo glucose homeostasis remains to be resolved.…”
Section: The Glucose-dependent Amplification Of Exocytosis In Human βmentioning
confidence: 99%
“…Islet SENP1 regulates glucose homeostasis in vivo by controlling the glucose-dependent amplification of insulin secretion. Reduced expression of SENP1 in islet cells protects against apoptosis (37), while increasing SUMOylation may impair insulin secretion (30,35). To determine the role of SENP1 in vivo, we generated SENP1 fl/fl mice and crossed them with the Pdx1-Cre line (49) to generate a tissue-selective knockout (herein referred to as pSENP1-KO; Figure 7A) mice and with the Pdx-CreER line (50) to generate an inducible β cell-specific knockout (herein referred to as iβSENP1-KO) ] i responses in pSENP1-KO islets ( Figure 8E).…”
Section: Senp1 Amplifies Exocytosis In β Cells Downstream Of Nadph Anmentioning
confidence: 99%